Nepal: Food Security, a Localized Institutional Irrigation Perspective on Public Irrigation Systems - Gautam, Upendra (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
Oriental philosophers have given top priority to food for orderly state affairs as well as personal wellbeing. In past, Nepal had a strong agricultural economy based on indigenous Farmer Managed Irrigation System (FMIS). State policy helped promote these systems. But contemporary Nepal opted for state control on irrigation water by building large scale public irrigation systems. In the last 43 years of planned development (1957-2002), the government has spent 70% of US$1.3 billion on these systems, covering 30% of the irrigated area in the country; the remaining 70% is with the FMIS. Despite the investment, these systems neither promoted themselves as an enterprise nor helped enhance agricultural productivity leading to social insecurity. This social insecurity is reflected in the country's increasing import of food, mass workforce exodus for employment abroad, and added socio-economic vulnerability due to climate change. Donor and government recommendations centered on (i) expansion of irrigated area, (ii) irrigation management transfer, and (iii) agriculture extension seem to have failed in Nepal. These failures asked for alternative institutional development solutions, whereas public irrigation systems are (i) localized to establish system's operational autonomy with ownership and governance, (ii) treated as a rich resource-base with water, land and labor, and (iii) recognized as cooperative enterprise of local stakeholders by law with authorities to enter into joint actions with relevant partners for promoting commercialization and environmental quality of irrigated agriculture. DOI: http://dx.doi.org/10.3126/hn.v11i1.7223 Hydro Nepal Special Issue: Conference Proceedings 2012 pp.95-99